Fledging Kelantan university inspired to take a leaf from Limkokwing’s book - Universiti Malaysia Kelantan, Canselori (2012)
Being one of the newest public tertiary institutions in Malaysia, University Malaysia Kelantan which was only set-up by the Malaysian Government last July, is looking forward that Limkokwing University of Creative Technology, share its experience on becoming a global university.